Neighborhoods’ Evaluation: Influence on Well-Being Variables - Ruiz, Cristina; Hernández-Fernaud, Estefanía; Rolo-González, Gladys; Hernández, Bernardo (Frontiers in Psychology, 2019)
The influence of neighbourhood characteristics on residents’ well-being and residential satisfaction has been widely studied, and has presented considerable variability. This study analyses the extent to which neighbourhood resources influence variables relating to well-being, and examines the relationship between neighbourhood resources and residents’ perceptions. The study was structured over two phases: 1) the neighbourhood resources were evaluated, and 2) 252 neighbourhood residents was interviewed. The results have shown that the observation by independent observers of neighbourhood resources is connected to residents’ perceptions of their neighbourhood. Residents’ perceptions of their neighbourhoods is associated with indicators of well-being, and residential satisfaction. Also, the reasons for living in the neighbourhood appear to be connected to the observed availability of resources and the perception of it. Wellbeing and residential satisfaction are the outcome of multiple aspects that are not limited to structural and material elements of neighbourhoods.